2003
DOI: 10.1074/jbc.m211059200
|View full text |Cite
|
Sign up to set email alerts
|

Rat Inositol 1,4,5-Trisphosphate 3-Kinase C Is Enzymatically Specialized for Basal Cellular Inositol Trisphosphate Phosphorylation and Shuttles Actively between Nucleus and Cytoplasm

Abstract: The calcium-liberating second messenger inositol 1,4,5-trisphosphate (Ins(1,4,5)P 3 ) is converted to inositol 1,3,4,5-tetrakisphosphate (Ins(1,3,4,5)P 4 ) by Ins(1,4,5)P 3 3-kinases (IP3Ks) that add a fourth phosphate group to the 3-position of the inositol ring. Two isoforms of IP3Ks (named A and B) from different vertebrate species have been well studied. Recently the cloning and examination of a human full-length cDNA encoding a novel isoform, termed human IP3K-C (HsIP3K-C), has been reported. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 46 publications
1
66
3
Order By: Relevance
“…A and B isoforms were found to be localized in both cytoskeleton and cytosolic, indicating a connection between cytoskeleton structure and InsP3K function. 5,[55][56][57] Consistent with this, similar with F-actin, InsP3KB is highly localized in the leading edge of polarized neutrophils. 16 In addition, since all three isoforms contain a calmodulin binding motif, the InsP3KB activity in neutrophils might also be regulated by calcium.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modusupporting
confidence: 63%
See 4 more Smart Citations
“…A and B isoforms were found to be localized in both cytoskeleton and cytosolic, indicating a connection between cytoskeleton structure and InsP3K function. 5,[55][56][57] Consistent with this, similar with F-actin, InsP3KB is highly localized in the leading edge of polarized neutrophils. 16 In addition, since all three isoforms contain a calmodulin binding motif, the InsP3KB activity in neutrophils might also be regulated by calcium.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modusupporting
confidence: 63%
“…The accelerated proliferation of granulocyte monocyte progenitors may be a result of enhanced PtdIns(3,4,5)P3/Akt signaling, which has been recently implicated in myelopoiesis. 13 This signaling pathway was previously thought to be dependent solely upon concentrations of PtdIns (3,4,5) P3 in the plasma membrane. 14,15 Recently, we demonstrated that two inositol phosphates, InsP7 and Ins(1,3,4,5)P4, compete for Akt-PH domain binding with PtdIns(3,4,5)P3 both in vitro and in vivo, providing another level of regulation for Akt membrane translocation and activation.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
See 3 more Smart Citations